A link-up resulted fatigue crack branching in Al–Cu–Mg alloy. (November 2016) - Lu, Songsong; Bao, Rui; Zhang, Ting; Fei, Binjun
Highlights: Significant fatigue crack branching is observed for Al–Cu–Mg alloy under both spectrum and constant loading. Branched cracks are classified into two types based on the branching processes at macroscopic scale. There is a relation between the appearance of the novel crack branching and load interval. The grain shapes and their interaction with the plastic zone size contribute to the appearance of this crack branching. The surface secondary crack is located near the plastic zone boundaries of the main crack. Abstract: Fatigue crack branching phenomena in Al–Cu–Mg alloy 2324-T39 are studied. Both spectrum and constant amplitude loading cases are examined. A novel type of crack branching process and mechanism is present, which results from the link-up of the secondary crack with the main crack. The grain shapes in 2324-T39 are different from those in the 2024 and 2524 alloys, and their interaction with the plastic zone size contributes to the appearance of this type of crack branching. FE analysis shows that the surface secondary crack is located near the plastic zone boundaries of the main crack.